1985
DOI: 10.1161/01.res.56.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reperfusion late in the phase of reversible ischemic injury. Changes in cell volume, electrolytes, metabolites, and ultrastructure.

Abstract: The acute effects of reperfusion on myocardium reversibly damaged by 15 minutes of severe ischemia in vivo, were studied. Changes in the adenine nucleotide pool, cell volume regulation, myocardial calcium, and ultrastructure were studied at the end of 15 minutes of ischemia and after 0.5, 3.0, and 20 minutes of reflow. Before reperfusion, adenosine triphosphate and the adenylate pool decreased by 63% and 44% of control, respectively, and the adenylate charge was reduced to 0.65. After 3 minutes of reperfusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
3
5

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(156 citation statements)
references
References 25 publications
6
142
3
5
Order By: Relevance
“…After 15 min of coronary occlusion, myocardial ATP concentration decreases substantially; it remains significantly depressed for many hours to days of reperfusion and usually returns to normal by 7 d (25,66,67). In other studies, creatine phosphate was shown also to fall markedly within minutes following coronary occlusion but to return to normal quite rapidly during coronary reperfusion.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 15 min of coronary occlusion, myocardial ATP concentration decreases substantially; it remains significantly depressed for many hours to days of reperfusion and usually returns to normal by 7 d (25,66,67). In other studies, creatine phosphate was shown also to fall markedly within minutes following coronary occlusion but to return to normal quite rapidly during coronary reperfusion.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…While this increase is dramatic in irreversibly injured cells, it may also be seen transiently and to a lesser extent in reversibly injured tissue (24,25). This so-called "explosive" cell swelling of irreversibly injured cells (26) appears to be caused by an ischemia-induced sarcolemmal abnormality which causes a serious defect in regulation of cell volume and which is associated with marked increases in tissue water, sodium, chloride, and calcium.…”
Section: Introductionmentioning
confidence: 99%
“…'°The xanthine oxidase reaction is of particular interest because large quantities of hypoxanthine, and its precursor inosine, accumulate rapidly in severely ischemic myocardium as a consequence of the degradation of the purine nucleotides."' 12 Especially when reperfusion is established, the xanthine oxidase reaction, fueled by an initially large substrate supply plus abundant oxygen resulting from reactive hyperemia, might produce an excessive load of superoxide anion. The latter might cause death of myocytes that would otherwise have survived the temporary period of ischemia.…”
mentioning
confidence: 99%
“…Electromicroscopic study also indicates that the recovery of cellular ultrastructure in reversibly injured myocardium occurs soon after reperfusion. 35 Previous studies in patients4'5 with occlusive or reperfused myocardial infarctions using Ti enhancing agent indicated that they could not be consistently distinguished using the conventional spin echo MR imaging technique. This discrepancy with the present study may be due to the fact that the long acquisition time of spin-echo imaging results in images displaying the steady-state phase of contrast media distribution, which may be influenced considerably by collateral flow and diffusion of contrast media in the infarcted region, even in occlusive infarctions.…”
Section: Characterization Of Myocardial Injuries Using Fast Mr Imaginmentioning
confidence: 99%